MENCIPTAKAN BUDAYA BELAJAR EFEKTIF DALAM MENINGKATKAN MUTU PENDIDIKAN (Studi Kasus Di MI Bustanul Ulum Brudu Jombang) - Arif, Moh. (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
This study aims to discuss how the process of creating an effective learning culture in MI Bustanul Ulum Brudu in improving the quality of education that is always associated with the process of teaching and learning activities with the goal of achieving quality and the quality of education in madrasas. The quality of education has been achieved because of the awareness and participation of all elements of education in MI Bustanul Ulum, so it can form an effective teaching and learning culture. For that, universally takes appropriate measures by way of intertwining komonikasi, the participation of all the elements of education, qualified human resources, planning and intensive guidance. All this can be carried out continuously either at the school or outside the madrasah. Keywords: cultural effective learning and improving the